تحضير ودراسة المتصل الثنائي Al,Cu,Ag/CdTe-p (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة الميزة I-V لمتصلات ثنائية من النوع Al,Cu,Ag/CdTe(p) من خلال ترسيب طبقات رقيقة من المعادن Al, Cu, Ag على فيلم رقيق من CdTe(p) محضر بثلاث طرق مختلفة: 1)   ترسيب الطبقات المتراكمة من العنصرين Cd  وTe. 2)   ترسيب مزيج من العنصرين   Cd وTe 3)   ترسيب مسحوق من البلورةCdTe . ثم أخضعت هذه الأفلام إلى المعالجة الحرارية فيما بعد الترسيب في الدرجة 400oC خارج حجره التخلية. تتصف هذه الأفلام ببنية مكعبة مركزية الوجوه (a»6.497Ao). تم حساب كلٍ من معامل الامتصاص وعرض العصابة المحظورة لهذه الطبقة. أشارت الميزة (I-V) بوضوح إلى خاصة تقويم التيار في هذه المتصلات نتيجة تشكل حاجز شوتكي. حدد كل من عامل المثالية (n»10) وكثافة تيار الإشباع وارتفاع حاجز شوتكي . فسر ارتفاع عامل المثالية بوجود طبقة رقيقة بينية من الأكسيد CdTeO3 التي تسبب ازدياداً في الكمون الداخلي Vbi وتأخراً في عتبة التيار (حول القيمة 0.6V). و قد تميز ارتفاع حاجز شوتكي بارتفاع الكهروسلبية للمعدن. لوحظ تحسن في قيم كثافة التيار في المتصلات المحضرة بالطريقة الأولى, وطابق هذا التحسن نقصان ارتفاع حاجز شوتكي، وفسر هذا الأمر نتيجة تزايد حجم الحبيبات البلورية لـ CdTe وزيادة بقايا عنصرTe, إذْ تسيطر النوعية (p) أكثر وتنخفض مقاومة المتصل الثنائي. In this research, the I-V characteristic of Al,Cu,Ag/CdTe-p diode is studied by depositing three layers of metals Al, Cu Ag on thin film of CdTe-p prepared by three different methods: • Depositing the accumulative layers of Cd and Te elements.• Depositing a mixture of Cd and Te elements.• Depositing a powder of CdTe monocrystal. These films were then thermally annealed after deposition at a temperature of 400oC outside the evacuation chamber. These films possess a face centered cubic structure (F.C.C.) (a= 6.497Ǻ). The  absorption coefficient and the energy band gap of thin layer were calculated. The I-V characteristic clearly indicates the current rectification property in there diodes a result of Schottky barrier formation. The ideality factor (n≈10) and the saturation current density  were determined. The height of Schottky barrier was been calculated. The increase in the ideality factor was interpreted by the interfacial layer of CdTeO3 oxide which caused an increase in the internal potential Vbi and a dilation in the current growth threshold around value 0.6 V. The height of Schottky barrier was characterized by an increase in the electronegative /value of the metal. An enhancement of the metal occurs in the current density values in the diodes prepared by the first method. Thin enhancement is accompanied by a decrease in Schottky barrier height and is related to the increase in the grain size and an increase in the remaining Te element where type (p) is enhanced greatly and the resistance of the diode is decreased.